Signal through the noise? Phylogeny of the Tachinidae (Diptera) as inferred from morphological evidence. (April 2014) - CERRETTI, PIERFILIPPO; O'HARA, JAMES E.; WOOD, D. MONTGOMERY; SHIMA, HIROSHI; INCLAN, DIEGO J.; STIREMAN, JOHN O.
Abstract The oestroid family Tachinidae represents one of the most diverse lineages of insect parasitoids. Despite their broad distribution, diversity and important role as biological control agents, the phylogeny of this family remains poorly known. Here, we review the history of tachinid systematics and present the first quantitative phylogenetic analysis of the family based on morphological data. Cladistic analyses were conducted using 135 morphological characters from 492 species belonging to 180 tachinid genera, including the four currently recognized subfamilies (Dexiinae, Exoristinae, Phasiinae, Tachininae) and all major tribes. We used characters of eggs, first‐instar larvae and adults of both sexes. We examined the effects of implied weighting by reanalysing the data with varying concavity factors. Our analysis generally supports the subfamily groupings Dexiinae + Phasiinae and Tachininae + Exoristinae, with only the Exoristinae and the Phasiinae reconstructed as monophyletic assemblages under a wide range of weighting schemes. Under these conditions, the Dexiinae, which were previously considered a well‐established monophyletic assemblage, are reconstructed as being paraphyletic with respect to the Phasiinae. The Tachininae are reconstructed as a paraphyletic grade from which the monophyletic Exoristinae arose. The Exoristinae are reconstructed as a monophyletic lineage, but phylogenetic relationships within the subfamily are largely unresolved. We further explored the evolution of oviposition strategy and found that the oviparous groups are nested within ovolarviparous assemblages, suggesting that ovipary may have evolved several times independently from ovolarviparous ancestors. This counterintuitive pattern is a novel hypothesis suggested by the results of this analysis. Finally, two major patterns emerge when considering host associations across our phylogeny under equal weights: (i) although more than 60% of tachinids are parasitoids of Lepidoptera larvae, none of the basal clades is unambiguously associated with Lepidoptera as a primitive condition, suggesting that tachinids were slow to colonize these hosts, but then radiated extensively on them; and (ii) there is general agreement between host use and monophyly of the major lineages.